2020
DOI: 10.1186/s13033-020-00383-6
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Theory of Change model of service user and caregiver involvement in mental health system strengthening in primary health care in rural Ethiopia

Abstract: Background The involvement of service users and caregivers is recommended as a strategy to strengthen health systems and scale up quality mental healthcare equitably, particularly in low-and-middle-income countries. Service user and caregiver involvement is complex, and its meaningful implementation seems to be a worldwide challenge. Theory of Change (ToC) has been recommended to guide the development, implementation and evaluation of such complex interventions. This paper aims to describe a ToC m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 87 publications
1
35
0
Order By: Relevance
“…A similar qualitative study on service user involvement in mental health system strengthening found unreliable medication supplies as a source of dissatisfaction among service users and service providers. Additionally, problems with regards to communication between service users and providers and a lack of evidence-based information about the medication options were also mentioned as barriers for involvement [54].…”
Section: Structural Stigmamentioning
confidence: 99%
See 1 more Smart Citation
“…A similar qualitative study on service user involvement in mental health system strengthening found unreliable medication supplies as a source of dissatisfaction among service users and service providers. Additionally, problems with regards to communication between service users and providers and a lack of evidence-based information about the medication options were also mentioned as barriers for involvement [54].…”
Section: Structural Stigmamentioning
confidence: 99%
“…Thus, using the community health workers especially health extension workers in rural Ethiopia could be important to enhance the community awareness due to their proximity to the community. Engaging the service users and caregivers in the awareness raising training could be effective in reducing public stigma [54].…”
Section: Interventions To Reduce Stigmamentioning
confidence: 99%
“…However, even as new primary care opportunities look promising, it is clear that Ethiopia faces many challenges (Workneh et al, 2020 ) related to the collaboration and integration of resources across the micro-, meso-, and macro- levels (Abayneh et al, 2020 ). The most obvious examples are that there is limited government support and push in, limited policies supported by funding, lack of education and training opportunities—and the ever present stigma related to mental health problems—all resulting in individuals experiencing disability, illnesses, premature mortality rates, and human rights abuses, among other challenges (Abayneh et al, 2020 ). The following suggestions are recommended to systematically strengthen the mental health care system and delivery of services in Ethiopia.…”
Section: Call For Collaborative Effortsmentioning
confidence: 99%
“…Health professionals, organizational leaders, and community leaders have a responsibility to work collaboratively to mobilize, support, and empower mental health treatment. Therefore, they must be willing to undergo capacity building, training, engage in research, and develop a commitment to create enabling environments (Abayneh et al, 2020 ). With collaborative actions across government officials, community leaders, research, university professionals, health care professionals, medical professionals, and even individuals in the community, the mental health service system can be widely accepted and adapted to fit the needs of the individuals within the culture.…”
Section: Call For Collaborative Effortsmentioning
confidence: 99%
“…Empowerment approaches are being used to equip service users with the skills, confidence and support they need to express their experiences and preferences to health workers and healthcare planners, with a view to effecting improvements in care (Kohrt et al ., 2020). Participatory action research is being used in rural Ethiopia to inform people with mental health conditions about their right to quality care and to mobilise people for action (Abayneh et al ., 2020). In the ASSET project (health system strengthening in sub-Saharan Africa: ), mental health service users will join CQI activities with health workers in learning health systems with the goal of improving care processes (including user experience) and the impact of care.…”
mentioning
confidence: 99%